Estimation with the nested logit model: Specifications and software particularities - Nadja Silberhorn; Yasemin Boztuğ; Lutz Hildebrandt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
Due to its ability to allow and account for similarities between pairs of alternatives, the nested logit model is increasingly used in practical applications. However the fact that there are two different specifications of the nested logit model has not received adequate attention. The utility maximization nested logit (UMNL) model and the non-normalized nested logit (NNNL) model have different properties, influencing the estimation results in a different manner. As the NNNL specification is not consistent with random utility theory (RUT), the UMNL form is preferred. This article introduces distinct specifications of the nested logit model and indicates particularities arising from model estimation. Additionally, it demonstrates the performance of simulation studies with the nested logit model. In simulation studies with the nested logit model using NNNL software (e. g. PROC MDC in SAS), it must be pointed out that the simulation of the utility function's error terms needs to assume RUT-conformity. But as the NNNL specification is not consistent with RUT, the input parameters cannot be reproduced without imposing restrictions. The effects of using various software packages on the estimation results of a nested logit model are shown on the basis of a simulation study.
Keywords: C13; C51; C87; M31; 330; nested logit model; utility maximization nested logit; non-normalized nested logit; simulation study; Logit-Modell; Modell-Spezifikation; Software; Vergleich; Simulation